Inhibitory effect of Lonchocarpus araripensis lectin in rat acute models of inflammation - PIRES,ALANA F. (2019)
Abstract: Dalbergieae tribe lectins, possessing binding affinity for galactose and mannose, present inflammatory and nociceptive effects, while those for N-acetylglucosamine are anti-inflammatory. Since the anti-inflammatory effect of the seed lectin of L. araripensis (LAL) had been already demonstrated in mice, this effect was presently evaluated in rat models of acute inflammation. LAL (0.01-1 mg/kg) was administered by intravenous (i.v.) route in male Wistar rats 30 min before paw edema induction by dextran or carrageenan, and peritonitis by carrageenan. LAL (1 mg/kg) was incubated with N-acetylglucosamine for allowing lectin-sugar interactions before injection into animals. LAL toxicity was evaluated by the parameters: body mass, organs weight, stomach macroscopy, hematological and biochemical dosage. Statistical analysis was performed by ANOVA and Bonferroni’s test (p<0.05). The paw edema induced by carrageenan (AUC: 0.96 ± 0.09) was inhibited by LAL about 39% (0-2 h) at all doses, and about 72% (3-5 h) at 0.1 and 1 mg/kg. The increase in the neutrophil migration stimulated by carrageenan was also inhibited by LAL (83%). In both models, LAL inhibitory effect was prevented by GlcNAc. The sub-chronic treatment with LAL was well tolerated by animals. LAL possesses anti-inflammatory effect via lectin domain, indicating potential modulator role in cellular inflammatory events.